The Columbus affair a novel - Berry, Steve, 1955- (New York : Random House Large Print, 2012)
When his beloved daughter falls in the clutches of a ruthless zealot, disgraced journalist Tom Sagan risks everything to embark on a perilous quest from Florida through Prague to Jamaica in search of an invaluable historical treasure.
Keywords: Columbus, Christopher -- Fiction; Treasure troves -- Fiction; Treasure hunts -- Fiction; Quests (Expeditions) -- Fiction; Journalists -- Fiction; Conspiracies -- Fiction; Florida -- Fiction; Jamaica -- Fiction; Vienna (Austria) -- Fiction; Prague (Czech Republic) -- Fiction; Suspense fiction; Large type books